Effects of noble metal nanoparticles on the hydroxyl radical scavenging ability of dietary antioxidants. (3rd April 2018) - Zhang, Hui; Jiang, Xiumei; Cao, Gaojuan; Zhang, Xiaowei; Croley, Timothy R.; Wu, Xiaochun; Yin, Jun-Jie
ABSTRACT: Noble metal nanoparticles (NPs) have been widely used in many consumer products. Their effects on the antioxidant activity of commercial dietary supplements have not been well evaluated. In this study, we examined the effects of gold (Au NPs), silver (Ag NPs), platinum (Pt NPs), and palladium (Pd NPs) on the hydroxyl radical (·OH) scavenging ability of three dietary supplements vitamin C (L-ascorbic acid, AA), (−)-epigallocatechin gallate (EGCG), and gallic acid (GA). By electron spin resonance (ESR) spin-trapping measurement, the results show that these noble metal NPs can inhibit the hydroxyl radical scavenging ability of these dietary supplements.